1996
DOI: 10.1002/jor.1100140602
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term study of the biochemistry and biomechanics of anterior cruciate ligament‐patellar tendon autografts in goats

Abstract: Summary: This study examined the change in type-I11 collagen concentration and hydroxypyridinium crosslink density of anlerior cruciate ligament-patellar tendon autografts and their correlations with Young's modulus of the anterior cruciate autografts and anterior cruciate controls for as long as 3 years after surgery. Fifteen adult female goats (two control and 13 experimental) were tested. Each experimental animal received an anterior cruciate ligament-patellar tendon autograft to the right knee. These anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 24 publications
0
51
1
2
Order By: Relevance
“…ACL reconstruction using a canine model shows early degenerative changes after this type of intraarticular procedure (Setton et al 1994, Jarvinen et al 1995. However, recent studies have reported long-term success, up to 3 years, when studying ACL reconstruction in a goat model (Jackson et al 1987, 1993, Ng et al 1996a. Our study suggests that the proposed ACL reconstruction technique can successfully restore the kinematics of an intact knee and permit observation of the strong interaction between ACL reconstruction and the MCL.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…ACL reconstruction using a canine model shows early degenerative changes after this type of intraarticular procedure (Setton et al 1994, Jarvinen et al 1995. However, recent studies have reported long-term success, up to 3 years, when studying ACL reconstruction in a goat model (Jackson et al 1987, 1993, Ng et al 1996a. Our study suggests that the proposed ACL reconstruction technique can successfully restore the kinematics of an intact knee and permit observation of the strong interaction between ACL reconstruction and the MCL.…”
Section: Discussionmentioning
confidence: 59%
“…Due to the difficult surgical technique for ACL reconstruction using smaller animals such as rabbits, the goat knee was chosen as an experimental model because it has had long-term success with ACL reconstruction (Ng et al 1996a, b). Furthermore, the use of robotic technology has facilitated the study of knee kinematics in multiple degrees-of-freedom (DOF) and determination of in situ forces in individual ligaments , Rudy et al 1996.…”
mentioning
confidence: 99%
“…LOX-derived cross-linking increases during adult tendon aging and wound healing (14,40), and it is believed to contribute significantly to mature tendon mechanical properties, although reports are inconsistent. LOX-derived hydroxylysyl pyridinoline (HP) cross-linking density was significantly correlated to elastic modulus in goat patellar tendon (41) but not in equine superficial digital flexor tendon (42) or human patellar tendon (43). In contrast, there are limited data of collagen cross-linking in embryonic tendon, and the focus was on a single embryonic time point without examining mechanical contributions (44).…”
Section: Discussionmentioning
confidence: 99%
“…The non-vascularized tendon graft subsequently undergoes a process of remodeling after implantation into the intraarticular environment by means of reorganizing its cellularity and extracellular matrix structure [40]. The process of graft tissue remodeling has been extensively studied in the past with respect to revascularization and reinervation, changes in cell morphology and distribu-tion, collagen fiber reorganization, and restoration of extracellular matrix protein distribution [3,4,6,[8][9][10]23,27,28,40]. So far the expression of cytoskeletal proteins as markers of phenotypic modulations of fibroblastic cells has not been investigated during cruciate ligament autograft remodeling.…”
Section: Introductionmentioning
confidence: 99%